Synthesis, structure elucidation and functionalization of sulfonamide [2]catenanes. Issue 18 (22nd July 2021) - Wang, Yu; Lu, Shuai; Wang, Xu-Qing; Niu, Yan-Fei; Wang, Heng; Wang, Wei
Abstract : A pyrene-functionalized [2]catenane with switchable optical output was constructed through a novel sulfonamide [2]catenane synthesized by a self-templation approach. Abstract : Novel sulfonamide [2]catenanes were successfully prepared through a self-templation approach. The catenated skeletons were confirmed by traveling-wave ion-mobility spectrometry (TWIMS) combined with gradient tandem mass spectroscopy (gMS 2 ). Moreover, two pyrene units were further introduced into the [2]catenane through the alkylation reaction of the sulfonamide moieties, resulting in the successful synthesis of a novel pyrene-functionalized [2]catenane which displayed a switchable optical output controlled by cation-induced conformation transformation.